HLA from Benchtop to Bedside - Eisenbrey, Arthur Bradley (Academic Press, 2021)
This book contains informations about HLA antigenes and histocompatibility testing. Intended for proffesional public.
Keywords: Histocompatibility Testing; alergologie a imunologie; testování histokompatibility; HLA antigeny; HLA Antigens